2012
DOI: 10.18597/rcog.173
|View full text |Cite
|
Sign up to set email alerts
|

Exactitud de la actividad de la telomerasa para el diagnóstico del virus del papiloma humano en mujeres con patología cervical en Armenia, Colombia, 2007

Abstract: Introducción: el cáncer de cérvix es un problema mundial de salud pública, con cerca de 500.000 casos diagnosticados anualmente, 68.000 de ellos en América Latina. En Colombia es la neoplasia maligna ginecológica más mortal y la segunda en incidencia después del cáncer de mama. La tasa de falsos negativos de la citología de cérvix es de 20-40%, lo que explica los casos presentes en la población oportunamente tamizada; la tipificación del virus del papiloma humano (VPH) y la actividad de la telomerasa son estud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…Furthermore, our study results are not only in accordance with those of several other groups who have identified telomerase activity in the majority of malignant tumors, but also in line with those who have identified telomerase activity in proliferative diseases, predisposing the development of malignant tumors [28][29][30][31][32] .…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, our study results are not only in accordance with those of several other groups who have identified telomerase activity in the majority of malignant tumors, but also in line with those who have identified telomerase activity in proliferative diseases, predisposing the development of malignant tumors [28][29][30][31][32] .…”
Section: Discussionsupporting
confidence: 92%